Impact of the Distance From the Cavotricuspid Isthmus to the Right Coronary Artery on First‐Pass Conduction Block During Cryoablation for Atrial Flutter - Minoru Nodera; Takashi Kaneshiro; Sadahiro Murota; Shinya Yamada; Masayoshi Oikawa; Yasuchika Takeishi (Journal of Arrhythmia)
ABSTRACT Background Cryoablation is an alternative to radiofrequency ablation for the treatment of cavotricuspid isthmus (CTI)‐dependent atrial flutter (AFL). However, the anatomical features that make achieving a CTI conduction block using cryoablation challenging remain unclear. Methods This study included 100 consecutive patients who underwent CTI cryoablation for AFL. Patients were divided into two groups: the first‐pass group, in which first‐pass CTI conduction block was achieved (n = 72) and the non‐first‐pass group, in which it was not achieved (n = 28). We analyzed the anatomical features and the temperature changes of the catheter during the first sequential CTI cryoablation. Results The distance from the CTI to the right coronary artery (RCA) in the first‐pass group was significantly longer than that in the non‐first‐pass group (p < 0.001). The time to reach nadir freezing temperature in the ventricular side of the CTI was significantly shorter in the first‐pass group than in the non‐first‐pass group (p < 0.001). The time to reach nadir freezing temperature at the ventricular side of the CTI correlated inversely with the distance from the CTI to the RCA (R = −0.410, p < 0.001). The distance from the CTI to the RCA was the only significant factor associated with achieving first‐pass CTI conduction block (odds ratio, 4.801, p < 0.001). Conclusions The distance from the CTI to the RCA was significantly associated with achieving first‐pass CTI conduction block by cryoablation. The warming effect of the RCA blood flow might prevent the CTI conduction block during cryoablation.